The Existence of Women Diamond Miners in Pumpung, South Kalimantan, XX-XXI Century - Subroto, Wisnu; Prawitasari, Melisa; Handy, Muhammad Rezky Noor (History Department, Semarang State University and Historian Society of Indonesia, 2023)
The stereotypes of people in rural and urban areas since the days of the kingdoms in the archipelago until the early days of Indonesian independence show a dichotomy of work between women and men. However, since Indonesia was in the New Order era, this stereotype began to fade, and there was a process of equality between women and men in all fields. In South Kalimantan, women started working in traditional mines, especially the diamond mine in Pumpung, Sungai Tiung Village, Cempaka District, Banjarbaru City. The data were collected and arranged chronologically according to the time of the incident by way of interviews and searching for documents or archives stored as records. The research results chronologically describe the journey of women's struggle through its historical process interestingly. The existence of women being equal to men continues to this day in the traditional diamond mining sector in Pumpung, Banjarbaru. Women began to work in jobs that required solid physical stamina to show that they were as capable as men in the work they had been doing for a long time, especially those recorded in the XX-XXI centuries. In conclusion, the role of women can no longer be underestimated, which is only as a housewife. Here the role of women becomes double; apart from being housewives, they are also partners equal to men.Keywords: Diamond miners, female miners, South Kalimantan Stereotip masyarakat dipedesaan maupun diperkotaan sejak zaman kerajaan-kerajaan di nusantara sampai zaman awal kemerdekaan Indonesia menunjukkan dikotomi pekerjaan antara perempuan dan laki-laki. Akan tetapi, sejak Indonesia di masa orde baru, stereotip ini mulai pudar dan terjadi proses kesetaraan antara perempuan dan laki-laki dalam segala bidang. Di Kalimantan Selatan, perempuan mulai bekerja di tambang tradisional khususnya tambang intan di Pumpung Kelurahan Sungai Tiung, Kecamatan Cempaka, Kota Banjarbaru. Data-data dikumpulkan dan disusun secara kronologis sesuai waktu kejadian dengan cara wawancara, dan pencarian dokumen atau arsip yang disimpan seperti catatan. Hasil penelitian secara kronologis menggambarkan secara menarik perjalanan perjuangan perempuan melalui proses menyejarahnya. Eksistensi perempuan untuk setara dengan kaum laki-laki terus berlanjut sampai sekarang ini di bidang penambangan intan secara tradisional yang ada di pumpung, Banjarbaru. Pekerjaan yang memerlukan stamina fisik yang kuat mulai digeluti kaum perempuan untuk menunjukkan bahwa mereka mampu seperti kaum laki-laki pekerjaan yang mereka geluti dari lama terutama yang terekam pada abad ke XX-XXI. Kesimpulannya peran perempuan tidak bisa lagi dipandang sebelah mata, yang hanya sebagai ibu rumah tangga. Disini peran perempuan menjadi ganda, selain sebagai ibu rumah tangga juga menjadi mitra kerja yang setara dengan kaum laki-laki.Kata Kunci: Penambang intan, Perempuan penambang intan, Kalimantan Selatan.